2016
DOI: 10.1007/s00227-016-2929-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the receiving assemblage and disturbance on the colonisation of an invasive species

Abstract: evaluated the effects of the presence of organic matter of a different source (simulating a disturbance event affecting different habitats) on colonisation. A model generalist invader, the isopod Cirolana harfordi, was introduced to patches of oyster beds with (1) undisturbed (live) assemblages, (2) disturbed assemblages, (3) organic matter (using organic matter of a different source), or (4) no assemblage or organic matter. Our results indicated that the presence of an assemblage (disturbed or not) fostered c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
6
0
3
Order By: Relevance
“…The consequences for the invaded ecosystem depend on characteristics of both the invading species and the ecosystem (Blackburn et al., ; Didham, Tylianakis, Hutchison, Ewers, & Gemmell, ; Henriksson, Wardle, Trygg, Diehl, & Englund, ; Kolar & Lodge, ; Ricciardi, Hoopes, Marchetti, & Lockwood, ; van Kleunen, Dawson, Schlaepfer, Jeschke, & Fischer, ). Ecosystems disturbed by humans are particularly prone to invasions as invaders frequently exploit disturbances (Bellard, Cassey, & Blackburn, ; Bugnot, Coleman, Figueira, & Marzinelli, ; Clark & Johnston, ; Hollings, Jones, Mooney, & McCallum, ; MacDougall & Turkington, ; Turner, ). However, the impact that invaders have on human‐disturbed ecosystems, and how this depends on other ongoing disturbances, are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences for the invaded ecosystem depend on characteristics of both the invading species and the ecosystem (Blackburn et al., ; Didham, Tylianakis, Hutchison, Ewers, & Gemmell, ; Henriksson, Wardle, Trygg, Diehl, & Englund, ; Kolar & Lodge, ; Ricciardi, Hoopes, Marchetti, & Lockwood, ; van Kleunen, Dawson, Schlaepfer, Jeschke, & Fischer, ). Ecosystems disturbed by humans are particularly prone to invasions as invaders frequently exploit disturbances (Bellard, Cassey, & Blackburn, ; Bugnot, Coleman, Figueira, & Marzinelli, ; Clark & Johnston, ; Hollings, Jones, Mooney, & McCallum, ; MacDougall & Turkington, ; Turner, ). However, the impact that invaders have on human‐disturbed ecosystems, and how this depends on other ongoing disturbances, are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystems disturbed by humans are particularly prone to invasions as invaders frequently exploit disturbances (Bellard, Cassey, & Blackburn, 2016;Bugnot, Coleman, Figueira, & Marzinelli, 2016;Clark & Johnston, 2011;Hollings, Jones, Mooney, & McCallum, 2016;MacDougall & Turkington, 2005;Turner, 2010). However, the impact that invaders have on human-disturbed ecosystems, and how this depends on other ongoing disturbances, are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…While classical invasion theory suggests that disturbance promotes invasion by freeing resources and reducing competition (Elton 1958 ; Davis et al 2000 ), its influence on invasion success appears to be complex, depending on species and ecosystem properties, type and timing of disturbance, and spatial scale (e.g., Lonsdale 1999 ; Melbourne et al 2007 ; Clark and Johnston 2011 ). An experimental study reported that colonization by the nonindigenous isopod Cirolana harfordi from Sydney Harbour, Australia was facilitated by the presence of an assemblage and influenced by the type of resident assemblage, with greater success on disturbed assemblages than undisturbed ones (Bugnot et al 2016 ). The type of disturbance was important, as an alternative source of organic matter simulating the effects of disturbance occurring upstream of the study site had no influence on colonization (Bugnot et al 2016 ).…”
Section: Attributes Of Recipient Ecosystemsmentioning
confidence: 99%
“…An experimental study reported that colonization by the nonindigenous isopod Cirolana harfordi from Sydney Harbour, Australia was facilitated by the presence of an assemblage and influenced by the type of resident assemblage, with greater success on disturbed assemblages than undisturbed ones (Bugnot et al 2016 ). The type of disturbance was important, as an alternative source of organic matter simulating the effects of disturbance occurring upstream of the study site had no influence on colonization (Bugnot et al 2016 ). In contrast, results of two empirical studies conducted in New Zealand suggest that disturbance had limited effects on the recruitment of U. pinnatifida (Morelissen et al 2016 ; South and Thomsen 2016 ).…”
Section: Attributes Of Recipient Ecosystemsmentioning
confidence: 99%
“…Biological invasions represent one of the principal threats to global biodiversity [ 1 ]. Either accidentally or intentionally, the introduction of exotic species [ 2 ] is responsible for the invasion of various species around the world, many of which have caused severe damage to the natural environment and wildlife [ 3 5 ]. Factors that determine which species will be successful invaders involve a number of complex interactions between the species and the biotic and abiotic components of the invaded region [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%